2010
DOI: 10.1002/ijc.25215
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of vitamin D, PTH and calcium and breast cancer risk—a prospective nested case–control study

Abstract: Previous studies indicate that calcium and its regulating hormones, i.e., parathyroid hormone (PTH) and vitamin D, might affect breast cancer risk. Evidence also suggests that this relationship could be influenced by menopausal status and BMI. We examined breast cancer risk related to prediagnostic serum levels of vitamin D (25OHD(2) and 25OHD(3)), PTH and calcium using a nested case-control design within the Malmö Diet and Cancer Study. There were 764 incident breast cancer cases, and 764 controls were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 69 publications
8
104
3
Order By: Relevance
“…21 Although this result is obviously consistent with ours, underlying mechanisms remain to be identified. As no effect modification by BMI was observed in several other prospective studies 23,[29][30][31]33 and case-control studies, 27,34 the differential association depending on BMI observed in our study may also be due to chance and requires further exploration. Heterogeneity in the association between circulating 25(OH)D and breast cancer risk was also detected across strata of HRT use at blood donation.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…21 Although this result is obviously consistent with ours, underlying mechanisms remain to be identified. As no effect modification by BMI was observed in several other prospective studies 23,[29][30][31]33 and case-control studies, 27,34 the differential association depending on BMI observed in our study may also be due to chance and requires further exploration. Heterogeneity in the association between circulating 25(OH)D and breast cancer risk was also detected across strata of HRT use at blood donation.…”
Section: Discussionmentioning
confidence: 42%
“…First, a crude model was built accounting for matching variables only, i.e., study center, age, menopausal status, exogenous hormone use, time of the day of blood collection, fasting status and phase of the menstrual cycle. Second, a multivariable model was built adjusting for potential confounders, i.e., body mass index (BMI, <25, 25-29.9 and 30 kg=m 2 ), age at first menses (<7 or missing, 7-10, 11-13 and 13 years), number of full-term pregnancies (1, 2, 3 and nulliparous), age at first full-term pregnancy (20,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and >30 years), breastfeeding (yes or no), alcohol consumption (<1.5, 1.5-9.9, 10-19.9, 20-29.9 and 30 g=day), smoking status (never, former and current), education level (none or primary school completed, technical or professional school, secondary school and longer education including university degree) and physical activity according to the Cambridge Physical Activity Index (inactive, moderately inactive, moderately active and active). A category for missing values was created for all adjustment variables.…”
Section: Statistical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The pth receptor is expressed in keratinocytes 29,30 , and a positive association between the risk of breast cancer and primary hyperparathyroidism has also been reported 31 . However, one study also showed no association between baseline serum pth and breast cancer risk 32 .…”
Section: Discussionmentioning
confidence: 99%